Tunable Non-linear Refraction Properties and Ultrafast Excited State Dynamics of Dicyanomethylene Dihydrofuran Derivative - Yang, Linpo; Li, Zhongguo; Wei, Taihui; Zhou, Liming; Li, Feng; Fang, Shaoming; Song, Yinglin (Frontiers in Chemistry, 2020)
The third order nonlinear optical response of a Dicyanomethylenedihydrofuran compound (DCDHF-2V) was investigated using Z-scan technique in picosecond and nanosecond time regimes. The results show that DCDHF-2V has excellent excited state nonlinear refraction properties on both time regime, and the nonlinear refraction index is also solvent-dependent in nanosecond regime. The excited state relaxation dynamics of DCDHF-2V was demystified via femtosecond transient absorption spectroscopy. The TA spectra reveal that the solvent viscosities have a substantial impact on the excited state relaxation of DCDHF-2V. The exotic photophysical phenomena in DCDHF-2V reported herein can provide new light to future development of small organic nonlinear optical materials with large nonlinear coefficients and fast response.